Analisis faktor-faktor yang mempengaruhi Audit Delay (studi empiris pada Perusahaan Pertambangan yang terdaftar di Bursa Efek Indonesia) - Imam Trianto; Raja Adri Satriawan; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Users of financial statements need information that is valid as a basis for decisions they make. In the conceptual framework of financial reporting stated that the timeliness of financial reporting is a major qualitative characterize in favor of the relevance of financial statements, so this will make the benefits of the financial statements will be reduced if the report was not available on time. Audit delay can be very detrimental to investors because it may increase information asymmetry and lead to rumors of capital market participants that create conditions in the capital markets is uncertain. The shorter the time period between the date of expiration of the fiscal year to the date of publication of the financial statements, the greater the benefits the users of financial statements. This study aimed to analyze the effect of company size, auditor opinion, size firm, solvency, and profitability to audit delay. Samples were selected using purposive sampling technique. The population is the entire mining company listed on the Indonesia Stock Exchange from 2012 until 2013. Hypothesis testing using multiple linear regression. From the test results, profitability variables significantly influence audit delay. While the variable size of the company, the audit opinion, the size of the firm, and no significant effect on the solvency of audit delay. The magnitude of the effect that (R2) by all variables together against the dependent variable of 12.3%, while the remaining 87.7% is influenced by other variables.Keywords: Audit delay, company size, audit opinion, firm size, solvency, profitability